PROBLEM BASED LEARNING (PBL) MODE DARING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN PENGUASAAN KONSEP ELASTISITAS DI SMA NEGERI 1 METRO - Dina Octora Sastaviana; Sutejo Sutejo; Nyoto Suseno; Friska Octavia Rosa; Eko Prihandono (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This research aims to improve critical thinking skills and mastery of the concept of elasticity through the application of PBL in online learning. The research was conducted at SMA Negeri 1 Metro in class XI IPA 1 in physics. Collecting data through documentation, pre-test and post-test, as well as questionnaires and interviews. Data analysis includes stages: data collection, data grouping, data checking, data description, synthesis, interpretation and drawing conclusions. This study obtained the results that the application of online mode PBL using google classroom and whatsapp group was effective in improving critical thinking skills and mastery of the concept of elasticity at SMA Negeri 1 Metro. The implication of this research is that it is recommended to use PBL in online mode to improve students' abilities. In addition, it is also necessary to choose online facilities that are affordable by students, and efforts should also be made to meet the needs of online learning facilities.